Probe-less friction stir spot processing (PFSSP) of AA5754/AA5083 joint by adding the B4C ceramics: Effect of shoulder features on mechanical properties and tribological behavior. (January 2023) - Liu, Shoufa; Zhang, Shaoguo; Vaira Vignesh, R.; Ojo, Olatunji Oladimeji; Mehrez, Sadok; Mohanavel, Vinayagam; Paidar, Moslem
Abstract: This study aims to improve the local shear behaviors of dissimilar spot welds of Al alloys through a particle-dispersion strengthening mechanism. Probe-less friction stir spot processing of the AA5083-H112 and AA5754-O alloys with B4 C ceramic reinforcement was investigated by modifying the tool shoulder surfaces. The smooth and scrolled shoulder tools were utilized for this study. The mechanical properties of the B4 C-reinforced spots were examined via the use of the miniaturized shear punch testing method and the tensile-shear test. At an unchanged process condition, the scrolled shoulder tool improved particle dispersion and dislocation density to an extent while it significantly reduced the average B4 C particle size from 60 to 6.71 μm more than that of the smooth shoulder tool. The scroll-pattern-assisted straining, material flow. The wear rate was significantly reduced in the sample fabricated with the scroll tool. The scrolled shoulder tool is recommended for the fabrication of the B4 C-reinforced spots. Highlights: The change in the tool shoulder surface has an insignificant impact on the shoulder indentation zone (SIZ). The sample fabricated with a scrolled tool has a slightly more dislocation density due to the high straining and particle disintegration. The scroll-pattern assisted straining, material flow and particle disintegration effects improved the shear force of the weld. The sheared surfaces of the sample produced by scrolled tool had more elongated dimples as compared to the sample produced by the smooth tool.